Performance analysis of the free surface lattice Boltzmann implementation in waLBerla - Plewinski, Jonas; Alt, Christoph; Köstler, Harald; Rüde, Ulrich (Proceedings in Applied Mathematics and Mechanics, 2024)
The free-surface lattice Boltzmann method uses a volume of fluid approach to simulate immiscible two-fluid flow problems. It divides the simulation domain into three distinct phases—gas, fluid, and interface—where computation within the gas phase is disregarded. The interface delineates a one-cell-thick layer between the first two phases, validated physically for implementation in the HPC C++ multiphysics framework waLBerla but lacking an exhaustive performance analysis. This paper aims to shed light on node-level performance on different architectures, employing continuous benchmarking, showing and analyzing weak scaling results on a modern HPC cluster, the Fritz supercomputer, and reporting energy consumption for the current implementation.<br